Monitoring competition jump load in Division I female collegiate volleyball athletes - Herring, C. H.; Fukuda, D. H. (Journal of Science in Sport and Exercise, 2022)
Aim: Tracking competition jump data provides a practical approach for assessing external load in volleyball. Purpose: The purpose of this study was to analyze competition jump load in collegiate volleyball players. Methods: Data from nine National Collegiate Athletic Association (NCAA) Division I female volleyball players from the 2018 and 2019 competitive seasons were analyzed. Jumps were individually assigned, time-stamped, and recorded for height. Jump count and rate overall and at low, moderate, high, and maximal intensities were calculated. One-way ANOVAs were used to assess the variance in mean jump height from all jumps (HTall) and top five jump heights from each match (HTtop5) across positions (middle blocker vs. outside hitter vs. right-side hitter), timepoint in season (early vs. mid- vs. late), match length (3- vs. 4- vs. 5-set match), and Friday/Sunday matches and two-way ANOVAs were used to analyze jump count and rate differences across intensities. Results: Significant differences in HTall and HTtop5 across positions (P < 0.001) were shown. Main effects were found for jump count and rate by position (P < 0.001) and for jump count by match length (P < 0.001). Significant intensity × position interactions for jump count and rate by position (P < 0.001) and by timepoint (P < 0.01) and jump count by match length (P < 0.001) were found. No statistically significant variance was observed in HTall or HTtop5 based on timepoint (P > 0.05), HTall, HTtop5, or jump rate by match length (P > 0.05), or HTall, HTtop5, jump count, or jump rate between Friday/Sunday matches (P > 0.05). Conclusion: Significant differences in competition jump height and load exist in NCAA Division I female volleyball players. Jump load alterations during training sessions may be warranted to maximize athlete readiness and performance.